Superior Activity of Non-interacting Close Acidic Protons in Al-rich Pt/H-*BEA Zeolite in Isomerization of N-hexane - Sazama, Petr; Kaucký, Dalibor; Morávková, Jaroslava; Pilař, Radim; Klein, Petr; Pastvová, Jana; Tabor, Edyta; Sklenák, Štěpán; Jakubec, Ivo; Mokrzycki, Lukasz (Elsevier Science BV, 2017)
Skeletal isomerization of linear alkanes, an essential reaction for the production of gasoline, relies on environmentally questionable chlorinated catalysts, whose activity exceeds that of alternative zeolite catalysts. This work describes an attempt to understand relations between the local arrangement of active sites and skeletal isomerization of n-hexane in order to adapt the structure of zeolite catalysts to increase the reaction rates. For this purpose, we used a combination of synthesis of zeolites of *BEA structural topology with unique density and distribution of strongly acid sites, analysis of the nature of the acid sites by H-1 MAS NMR spectroscopy and FTIR spectroscopy of the OH groups and adsorbed d(3)-acetonitrile, UV-vis-NIR spectroscopy of carbocations formed by protonization, and kinetic analysis. We demonstrate that the high density of non -interacting but close and strongly acidic structural hydroxyl groups significantly lower the activation barrier in the isomerization reaction compared to far-distant acid sites. The organotemplate-free synthesized Al-rich Pt/H-*BEA zeolite (Si/AI 4.2) with an unparalleled high concentration of the non -interacting close H+ ions balancing the charge of the Al-Si-Al sequences forming a wall between the two channels yields 6 times higher reaction rates compared to state-of-the-art Si-rich Pt/H-zeolite catalysts.
Vynikající účinek nereagujících blízkých kyselých protonů v zeolitu na hliník bohaté Al-richPt / H- * BEA v izomerizaci n-hexanu
Keywords: Isomerization; Alkanes Hexane; Zeolites; Al-rich beta (*BEA); Mordenite; Izomerizace; alkany; hexan; zeolity; Al-rich beta (*BEA); mordenit